Universidade corporativa: uma análise das práticas de formação continuada dos colaboradores do Serviço de Apoio às Micro e Pequenas Empresas da Paraíba - SEBRAE/PB - Souza, Luciano de Holanda de (2018)
Since the end of the 19th century, the organizations in Brazil have dedicated with more keen to the training processes of their employees. The ongoing training and the practices of corporate education have been adopted in the maintenance of competitive advantage in the organizations that develop themselves and recognize the value of information and knowledge. The present research analyzed such practices in the Brazilian Micro and Small Business Support Service in Paraíba – SEBRAE/PB, which is an institution directed to the creation and dissemination of applicable knowledge to the management of other organizations. As an general objective, the SEBRAE Corporate University was analyzed as a practice of ongoing training of the employees who are part of the staff of analysts of SEBRAE/PB. The methodology adopted in the analysis is classified as exploratory and descriptive, in relation to its objectives. In turn, it was classified as a quantitative and qualitative approach in relation to the data nature. The research tools were based on the indicators that were built in the light of the theoretical foundation of Eboli (2004), the seven principles of a strategic plan of corporate education. The results point to a relevant. However, it is evidenced in the analysis of the collected data that the offer of educational solutions by the SEBRAE Corporate University is not enough to satisfy the need of the analyst in his ongoing training. They evaluate in a positive manner the influence of the SEBRAE Corporate University in the promotion of ongoing training and in the professional performance. It is also pointed that the main benefit generated by the corporate university is the contribution in the learning of new knowledge. The analysis in the light of the principles of corporate education of Eboli concluded that such principles are implanted in the practices of the SEBRAE Corporate University. However, the degree of some principles needs to be expanded, in order to be ratified the excellence of the practice and that be recognized its relevance to the ongoing training of the employees of SEBRAE/PB. With this research, it is aimed to contribute to the formation of applicable knowledge to the organizations which recognize the importance of knowledge in the ongoing of their employees.